How Sustainability Labels, Minimalist Design, and Brand Activism Influence Premium Product Perception - Umpusinga, Hasrun Afandi; Purwoko, Bambang (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of sustainability labels, minimalist design, and brand activism on consumers’ perception of premium products. Drawing from signaling theory and consumer psychology, the research examines how these factors serve as signals that shape premium product evaluation. Using survey data analyzed through multiple regression, the findings reveal that all three variables significantly and positively impact premium product perception, with sustainability labels exerting the strongest effect. Minimalist design and brand activism also contribute meaningfully by enhancing perceived elegance and aligning brand values with consumer ethics. The results underscore the importance of integrating ethical certifications, refined aesthetics, and authentic activism in premium branding strategies to meet the evolving demands of conscious consumers. Implications for marketers and suggestions for future research are discussed.